2010
DOI: 10.1155/2011/129045
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Dandelion Root Extract in Inducing Apoptosis in Drug‐Resistant Human Melanoma Cells

Abstract: Notoriously chemoresistant melanoma has become the most prevalent form of cancer for the 25–29 North American age demographic. Standard treatment after early detection involves surgical excision (recurrence is possible), and metastatic melanoma is refractory to immuno-, radio-, and most harmful chemotherapies. Various natural compounds have shown efficacy in killing different cancers, albeit not always specifically. In this study, we show that dandelion root extract (DRE) specifically and effectively induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Increasing evidence from studies have shown that herbal extracts can induce apoptosis and arrest cell cycle in various cell types, such as BCSCS, without affecting healthy cells. Some recent studies have shown that extracts from dandelion Taraxacum officinale, also known as Dandelion Anticancer, could inhibit the proliferation of human melanoma cells (Chatterjee et al, 2011), breast cancer cells, prostate cancer cells (Sigstedt et al, 2008), and cervical cancer cells (Ketut Edy Sudiarta, 20165). Studies showed that dandelion extracts could induce cell death via the tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) pathway.…”
Section: Dandelion Extracts Inhibited the Breast Cancer Stem Cell Promentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence from studies have shown that herbal extracts can induce apoptosis and arrest cell cycle in various cell types, such as BCSCS, without affecting healthy cells. Some recent studies have shown that extracts from dandelion Taraxacum officinale, also known as Dandelion Anticancer, could inhibit the proliferation of human melanoma cells (Chatterjee et al, 2011), breast cancer cells, prostate cancer cells (Sigstedt et al, 2008), and cervical cancer cells (Ketut Edy Sudiarta, 20165). Studies showed that dandelion extracts could induce cell death via the tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) pathway.…”
Section: Dandelion Extracts Inhibited the Breast Cancer Stem Cell Promentioning
confidence: 99%
“…TRAIL is a member of the TNF super family that can initiate apoptosis by activation of death receptor 4 (DR4/ TRAILR-1) and death receptor 5 (DR5/TRAILR-2). Since TRAIL can induce apoptosis in cancer cells, including breast cancer cells, without causing toxicity to normal cells (Chinnaiyan et al, 2000;Keane et al, 1999;Walczak et al, 1999), strategies which target TRAIL represent safe alternatives for cancer therapy development (Abdelhamed et al, 2013).…”
Section: Dandelion Extracts Inhibited the Breast Cancer Stem Cell Promentioning
confidence: 99%
“…14 Recent investigations have shown that dandelion root extract (DRE) has the ability to selectively induce apoptosis in human melanoma and leukemia cells, with no toxicity to noncancerous peripheral blood mononuclear cells. 15,16 Whether DRE can induce programmed cell death in highly aggressive and resistant human pancreatic carcinoma cell lines remains unknown. In this study, we show the efficacy of DRE in inducing apoptosis in a dose-and timedependent manner in aggressive human pancreatic cell lines (BxPC-3 and PANC-1).…”
mentioning
confidence: 99%
“…In parallel, similar experiments in noncancerous normal human fetal fibroblasts indicate that DRE selectively targets human pancreatic cancer cells, confirming results from previous studies. 15,16 Early activation of caspase-8 and subsequent activation of caspase-3 indicate that apoptosis induction by DRE is caused by activation of the extrinsic pathway of apoptosis. Interestingly, we observed that DRE induced a prodeath form of autophagy in human pancreatic cancer cells.…”
mentioning
confidence: 99%
“…Taraxinic acid and sesquiterpene lactone have been found to be the most allergic components in dandelion, causing allergic contact dermatitis and reactions in sensitive individuals [149]. In a study evaluating dandelion root extract efficacy in drugresistant human melanoma cells, the root extract was revealed to be non-toxic to normal human cells (while it was toxic to human melanoma cells) [150].…”
Section: Toxicity Of Dandelionmentioning
confidence: 99%